2021
DOI: 10.1177/00222194211011580
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Data-Based Decision-Making on Low-Performing Readers in General Education Classrooms: Cumulative Evidence From Six Intervention Studies

Abstract: In most general education classrooms in Germany, students with and without special educational needs are taught together. To support teachers in adapting instruction to these heterogeneous classrooms, we have developed learning progress assessment (LPA) and reading instructional materials, the Reading Sportsman (RS) in line with the theoretical framework of data-based decision-making, which has led to beneficial effects in several studies. However, data from these studies have not been analyzed to examine effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…For example, identifying struggling students' learning needs led to great consent among the teachers. This emphasizes the added value of DBDM in the school context: Theoretical articles and empirical studies have cited the determination of appropriate instructional steps for students' individual learning needs as a reason for data usage (Mandinach and Gummer, 2016;Prenger and Schildkamp, 2018;Peters et al, 2021). Similarly, research on educational technologies has reported on the potential of DLP to provide information about students' needs from learning data (Greller et al, 2014;Schaumburg, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, identifying struggling students' learning needs led to great consent among the teachers. This emphasizes the added value of DBDM in the school context: Theoretical articles and empirical studies have cited the determination of appropriate instructional steps for students' individual learning needs as a reason for data usage (Mandinach and Gummer, 2016;Prenger and Schildkamp, 2018;Peters et al, 2021). Similarly, research on educational technologies has reported on the potential of DLP to provide information about students' needs from learning data (Greller et al, 2014;Schaumburg, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Under the term of DBDM-which refers to "the systematic collection and analysis of different kinds of data to inform educational decisions" (Mandinach and Schildkamp, 2020, p. 1)-learning data in teaching and learning processes became a major focus of research. Among others, DBDM can help teachers determine instructional steps that meet learners' diverse needs (Mandinach and Gummer, 2016;Prenger and Schildkamp, 2018;Peters et al, 2021). Because DBDM focuses on every child, not just children with identified special educational needs, it is consistent with the idea of an inclusive school environment (Mandinach and Gummer, 2013;Knickenberg et al, 2020).…”
Section: Usage Of Learning Data For Instructional Designmentioning
confidence: 90%
See 1 more Smart Citation
“…In Britain, students with reading difficulty have shown little evidence of improvement even when schools implement support systems (Ofsted, 2010). In Germany, there are no federal systems to improve outcomes for individual students (Blumenthal et al, 2021), and evidence suggests that efforts to support students with intensive reading needs at the classroom level do not improve reading outcomes (e.g., Peters et al, 2021). Globally, Progress in International Reading Literacy Study (PIRLS) data show that the gap between students with and without reading difficulty is persistent and may be growing (Mullis et al, 2017).…”
Section: Role Of Multi‐tier Support Systems In Addressing Academic Needsmentioning
confidence: 99%
“…At the same time, the data supporting the value of DBDM systems have come mostly from studies of school‐wide implementation, not from studies of DBDM systems like DBI designed to support individual students. Moreover, extant data are not especially positive: A study of DBDM implementation in Germany showed that implementation led to improved reading outcomes for most students but not those with disabilities (Peters et al, 2021). In short, DBDM requires that many systems features are already in place, but the conditions under which DBDM for students with persistent academic difficulties (e.g., DBI) is successful have not been thoroughly explored.…”
Section: Role Of Multi‐tier Support Systems In Addressing Academic Needsmentioning
confidence: 99%